Molecular-Level Modifications Induced by Photo-Oxidation of Lipid Monolayers Interacting with Erythrosin - Aoki, Pedro H B (Langmuir : the ACS journal of surfaces and colloids, 2016)
Incorporation into cell membranes is key for the action of photosensitizers in photomedicine treatments, with hydroperoxidation as the prominent pathway of lipid oxidation. In this paper, we use Langmuir monolayers of 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC) and 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) as cell membrane models to investigate adsorption of the photosensitizer erythrosin and its effect on photoinduced lipid oxidation. From surface pressure isotherms and polarization-modulated infrared reflection-absorption spectroscopy (PM-IRRAS) data, erythrosin was found to adsorb mainly via electrostatic interaction with the choline in the head groups of both DOPC and DPPC. It caused larger monolayer expansion in DOPC, with possible penetration into the hydrophobic unsaturated chains, while penetration into the DPPC saturated chains was insignificant. Easier penetration is due to the less packed DOPC monolayer, in comparison to the more compact DPPC according to the monolayer compressibility data. Most importantly, light irradiation at 530 nm made the erythrosin-containing DOPC monolayer become less unstable, with a relative surface area increase of ca. 19%, in agreement with previous findings for bioadhesive giant vesicles. The relative area increase is consistent with hydroperoxidation, supporting the erythrosin penetration into the lipid chains, which favors singlet oxygen generation close to double bonds, an important requirement for photodynamic efficiency